Pelatihan pembuatan rumah tanaman (greenhouse) bagi kelompok kerahiman Stasi Gereja St. Yoseph Dusun Sarsang, Kecamatan Tanah Miring, Kabupaten Merauke: Plant House Making Training (Greenhouse) For Church Mercy Group St. Yoseph Sarsang Village, Tanah Miring, Merauke District - Muchlis Alahudin; Henry Raubaba; Micahel Mita; Yohanes Sinambela (IGKOJEI: Jurnal Pengabdian Masyarakat, 2023)
Church of Mercy Group St. Yoseph Dusun Sarsang was founded in 2018, has several types of activities, including; 1). Visiting and praying for the sick, 2). Worship in Goa Maria, 3). Sunday Service, 4). Song, apart from religious activities, there are also non-religious activities, namely; 1). Farming, 2). Selling, 3). Crafts and 4). Cullinary art. The purpose of this service is to provide training to the Church's Mercy Group on how to grow crops in a better way by using greenhouses using used bottle waste as roof covering material. The methods used are Experimental and Applicative, counseling and training on making greenhouses. The mechanism is in 4 stages, namely (1) Observation, (2) Greenhouse work, (3) Management of Service Permits and (4) Implementation. The results of this service are that hoped the people of Sarsang village can understand and understand the process of making a simple greenhouse with these skills, the hope is that the community can carry out agricultural/livestock/fishing activities with other models independently, and it is also hoped that the presence of a greenhouse can meet food needs, in this case vegetables, and can increase income from cultivation / livestock / fishery in the Greenhouse. greenhouse for St. Church's Mercy Group. Yoseph Dusun Sarsang uses structural materials and greenhouse construction using wood, for the walls using Paranet 80% while the roof covering uses used bottle roofs with the number of used bottles used + 1190 used bottles, greenhouse area + 28 m2 (4 m x 7 m).